Propositions on right-wing populism: Available, excessive, optimistic. (June 2022) - Anderson, Ben; Secor, Anna
Abstract: Every discourse on right-wing populism is, more or less explicitly, a discourse on affect. From claims that right-wing populism emerges from a background of racialized resentment or the anger of the 'left behind', through to analyses of how populist politicians mobilized hatred and rage in a 'post-truth era', attempts to explain the emergence and electoral success of contemporary right-wing populism have centered affect. In the midst of the turbulence of post 2007 financial crisis politics, the discourse on right-wing populism has repeated the tensions and ambivalences that surround affective politics per se – with populism simultaneously serving as a warning of what an affect-based politics might become, whilst also seeming to offer a lesson for the liberal-left in how to mobilize and move people otherwise disaffected. In this paper we supplement this attention to affect, and step outside of this tensed relation, by articulating the structure of feeling of contemporary right-wing populism in the U.S.A and UK. We do so through the form of the proposition, finding in the proposition a style of inhabiting an impasse that (re/dis)orientates attention and opens up disagreement and further discussion. In the first proposition - populism is available – we explore questions of definition, settling on how the discursive emptiness of populism allows for its constant articulation. Populism is excessive – the second proposition – shifts to emphasizing the affective fullness of populism, following how this fullness plays out in registers such as fun. Our third proposition – populism is optimistic – argues that right-wing populism is dependent on a 'temporal loop' optimism where the future to come blurs with the past that was. We conclude with some reflections on the future of this affect structure in light of the January 2021 events in the US Capitol and the electoral defeat of Donald J Trump.